Government and politics in Africa - TORDOFF, William (Macmillan Pres LTD, 1997)
his updated edition on African government and politics provides comprehensive coverage of the contemporary politics of the continent set in a clear historical context. Each chapter has been thoroughly revised to take account of developments and research and a completely new chapter added on political liberalisation and economic reform. This edition also gives extra coverage of North and South Africa and of such key issues as debt, the Aids epidemic, the position of women and the politics of patronage.